2018
DOI: 10.1016/j.athoracsur.2018.05.074
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Mitral Valve Repair in Older Individuals: An Analysis of The Society of Thoracic Surgeons Database

Abstract: The rMVr procedure was associated with less atrial fibrillation, less frequent transfusion requirement, and shorter intensive care unit and hospital stay, without a significant difference in 3-year mortality, heart failure readmission, or mitral valve reintervention. In older patients, rMVr confers short-term advantages without a detriment to midterm outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
66
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(66 citation statements)
references
References 15 publications
0
66
0
Order By: Relevance
“…Selection of patients comes in many forms and often has taken place even before patients arrive to the surgeon [3]; the net result is that patients who end up in robotic operating rooms are a highly selected, low-risk cohort, operated on by a highly selected group of surgeons. Table 1 shows some key differences that are evident in the propensity-matched cohort derived by Wang and associates [1]. The two populations are far from similar.…”
Section: Invited Commentarymentioning
confidence: 99%
See 1 more Smart Citation
“…Selection of patients comes in many forms and often has taken place even before patients arrive to the surgeon [3]; the net result is that patients who end up in robotic operating rooms are a highly selected, low-risk cohort, operated on by a highly selected group of surgeons. Table 1 shows some key differences that are evident in the propensity-matched cohort derived by Wang and associates [1]. The two populations are far from similar.…”
Section: Invited Commentarymentioning
confidence: 99%
“…In this issue of The Annals of Thoracic Surgery, Wang and colleagues [1] present a propensity-matched comparison of patients older than 65 years of age who received robotic compared with sternotomy mitral valve repair. The assumption of this study, and of several prior comparative analyses of robotic versus sternotomy mitral valve repair, is that propensity matching produced similar populations, differing only in the approach used to access the mitral valve.…”
Section: Invited Commentarymentioning
confidence: 99%
“…For fully developed pathoanatomically directed MV programs, robotic technology may become a tool not just reserved for the Grade 1 patients with straightforward pathology, but a standard approach for all Grades and all-comers including the elderly or infirm as a manner in which to perhaps actually decrease the morbidity of a sternotomy approach. 16,29,30…”
Section: Future Directionsmentioning
confidence: 99%
“…Wang et al reviewed the Society of Thoracic Surgeons database and compared surgical outcomes of robotic and surgical mitral valve repair in patients aged 65 years and older [9]. They found that robotic mitral valve repair was associated with less postoperative atrial fibrillation, less blood transfusion, and shorter intensive care unit and hospital stay compared with surgical mitral valve repair without a difference in 3-year mortality, heart failure readmission, or mitral valve reintervention.…”
Section: Introductionmentioning
confidence: 99%